Faktor Isi Rumah, Status Pemakanan dan Kesihatan yang Mempengaruhi Keupayaan Kognitif Am Kanak-kanak Orang Asli - Abdullah, Haslinah (2009)
The purpose of the study was to determine the relationship between household factors and children’s health and nutritional status with the general cognitive ability of Orang Asli children aged 2.5-8.5 years old. This cross section research had interviewed 126 Orang Asli mothers using survey forms to obtain the information on household demographics, socio-economic status, food security and children’s health status. The Radimer/Cornell Hunger and Food Insecurity instrument was used to determine the level of household food security while a three days 24-hour Diet Recall method was used to determine the quantity and quality of food intake of Orang Asli children. Orang Asli children were measured for weight and height and the measurements were transformed into three growth indices of height-for-age, weight-for-age and weight-forheight. The cognitive ability of the Orang Asli children was determined using McCarthy Scales of Children’s Abilities. The findings showed that the socio-economic status of the Orang Asli households was low, indicated by a high percentage of poverty (68.3%) and hard core poverty (28.3%) households. One third (21.7-26.7%) of the Orang Asli parents had no formal education, majority of them (46.7-50.8%) had education until primary school and only small percentage (22.6-31.6%) had education up to secondary school and tertiary education. About 88.3% of the Orang Asli households experienced varying levels of household food insecurity. There were 82.4% stunted, 84.9% underweight and 39.4% wasted children, respectively. The Orang children had low intake of most food groups such as vegetables, fruits, meat and meat products, as well as milk and milk products. The low food group intakes could well explain the inadequate intake of energy, vitamin A, vitamin C, niacin and calcium. The Orang Asli children also showed low cognitive ability with more than half (57.8%) had weak and very weak general cognitive scores. The mean scores of verbal and quantitative indices were below the mean scale indices which indicate that their abilities in speech and basic operational mathematics were below the average scores of children with the same chronological age. Whereby, the mean score of performance-perception which was near to the mean scale index showed that the children of Orang Asli had a good reasoning. Normal growth children of mothers with higher education and income had better general cognitive ability compared to children who were stunted (F=3.93;p<0.05) and underweight (F=7.23;p<0.01) of mothers with low education (F=3.83;p<0.05), no income (F=-2.05;p<0.05). The Pearson Product-moment Correlation Analysis indicated that the level of mothers’ education (r=0.220;p<0.05), energy intake (r=0.192;p<0.05), vitamin A intake (r=0.204;p<0.05) and weight-for-age (r=0.215;p<0.05) were related to the cognitive ability of the Orang Asli children. The Multiple Linear Regression results showed that mother’s education (β=0.117;p<0.05) and children’s height-for-age (β=0.229;p<0.05) were important factors contributing to cognitive ability of the Orang Asli children. Efforts to address cognitive development as well as educational achievement of Orang Asli children should take into account mother’s education level and child’s health and nutritional status. Socioeconomic, health and nutrition programs targeted towards the women and children are important in order to promote the wellbeing of the Orang Asli children.